Should we worry about filter bubbles? - Frederik J. Zuiderveen Borgesius; Damian Trilling; Judith Möller; Balázs Bodó; Claes H. de Vreese; Natali Helberger (Internet Policy Review, 2016)
Some fear that personalised communication can lead to information cocoons or filter bubbles. For instance, a personalised news website could give more prominence to conservative or liberal media items, based on the (assumed) political interests of the user. As a result, users may encounter only a limited range of political ideas. We synthesise empirical research on the extent and effects of self-selected personalisation, where people actively choose which content they receive, and pre-selected personalisation, where algorithms personalise content for users without any deliberate user choice. We conclude that at present there is little empirical evidence that warrants any worries about filter bubbles.
Keywords: 300; Filter bubble; Personalisation; Selective exposure